A QUANTUM ESPRESSO STUDY OF NITROGEN DOPED GRAPHENE USING DENSITY FUNCTIONAL THEORY - A.B. AHMED; SAID, MANSUR; A. A. SISA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Nitrogen doped graphene has attracted attention because of the abundance of nitrogen and high performances of graphene. Graphene is an allotrope of carbon that takes the shape of a plane of sp2-bonded atoms with a molecular bond length of 0.142 nm. Despite the material's unusual characteristics, such as being the thinnest known material but the strongest, and a brilliant conductor of both heat and electricity, it lacks a band gap.Quantum Espresso was used to investigate the structural and electronic properties of graphene nanosheet. It was observed that pure graphene produces zero energy gap while 0.32 when the hydrogen atom was doped. Different patterns were observed in Total Density of State (TDOS) and Projected Density of State (PDOS) due to the doping effect.